Rancang Bangun Alat Pendeteksi dan Pengusir Hama Tanaman Kangkung menggunakan Sensor Pir dan Cairan Peptisida Berbasis Internet Of Things (IOT) - Putri Mayang Sari; Novriyenni Novriyenni; Milli Alfhi Syari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to design and build a tool for detecting and repelling pests on kale plants using Passive Infrared (PIR) sensors and Internet of Things (IoT) based pesticide liquid which can be controlled via the Telegram application. This system works by detecting the movement of pests using a PIR sensor, which then activates the mechanism for automatically spraying pesticide liquid to repel pests. Users can monitor and control this tool in real-time via Telegram, providing flexibility in plant monitoring. Data from sensors is sent to the IoT platform and integrated with Telegram to provide remote notifications and control. Test results show that this tool can detect the presence of pests with high accuracy and is effective in repelling pests from the kale plant area. It is hoped that the implementation of this tool can help farmers maintain the quality and quantity of their kale harvest in a more efficient and environmentally friendly manner.